Persistence of Antibiotic-Resistant Escherichia coli Strains Belonging to the B2 Phylogroup in Municipal Wastewater under Aerobic Conditions - Hui Xie; Yoshitoshi Ogura; Yoshihiro Suzuki (MDPI AG, 2022)
Escherichia coli is classified into four major phylogenetic groups (A, B1, B2, and D) that are associated with antibiotic resistance genes. Although antibiotic-resistant E. coli is commonly detected in municipal wastewater, little is known about the relationship between the phylogenetic groups and antibiotic-resistant E. coli in wastewater. In this study, the survival of E. coli in wastewater and the changes to the relationships between each phylogroup and the antibiotic-resistant profiles of E. coli isolates from wastewater were investigated under aerobic conditions for 14 days. The isolates were classified into the phylogroups A, B1, B2, and D or others by multiplex PCR. In addition, the susceptibility of the isolates to 11 antibiotics was assessed with the minimum inhibitory concentration (MIC) assay. While E. coli counts decreased in the wastewater with time under aerobic conditions, the prevalence of phylogroup B2 had increased to 73% on day 14. Furthermore, the MIC assay revealed that the abundance of antibiotic-resistant E. coli also increased on day 14. After batch-mixing the experiments under aerobic conditions, the surviving antibiotic-resistant E. coli included mainly multidrug-resistant and beta-lactamase-producing isolates belonging to phylogroup B2. These results suggest that the phylogroup B2 isolates that have acquired antibiotic resistance had a high survivability in the treated wastewater.